Assigning Value to Clinical Information – A Major Limiting Factor in the Implementation of Decision-Support Systems - de Dombal, F. T. (Methods of Information in Medicine, 1996)
This paper deals with a major difficulty and potential limiting factor in present-day decision support - that of assigning precise value to an item (or group of items) of clinical information. Historical determinist descriptive thinking has been challenged by current concepts of uncertainty and probability, but neither view is adequate. Four equations are proposed outlining factors which affect the value of clinical information, which explain some previously puzzling observations concerning decision support. It is suggested that without accommodation of these concepts, computer-aided decision support cannot progress further, but if they can be accommodated in future programs, the implications may be profound.
Keywords: Diagnosis; Uncertainty; Probability